An investigation on substitutability between banksaving and insurance in Chinese context - Zhang, Zihan (2006)
The dissertation investigates the feasibility of diversifying saving through the insurance market. Cross section data has been collected through a randomly distributed questionnaire. Three hypotheses were tested to identify the substitutability between saving and insurance products. Diverse findings are presented. Only commercial old-age insurance reduced saving rate significantly, precautionary saving has not been substituted by health insurance and property insurance, while the substitute effect between retirement expenditure and old-age insurance is more evident.